STUDI FORMULASI GEL EKSTRAK KULIT RARU (COTYLELOBIUM MELANOXYLON PIERRE) SEBAGAI AGEN ANTIBAKTERI - Michelle Veronica Gulo gulo; Roy Indrianto Bangar; Refi Ikhtiari (Jurusan Farmasi, Poltekkes Kemenkes Palembang, 2026)
Acne is a skin condition affecting adolescents and young adults, characterized by an imbalance in the skin microbiome, excessive sebum production, and the accumulation of keratin, triggered by the bacteria Propionibacterium acnes, a significant pathogenic factor. Acne can be treated with antibiotics, but long-term antibiotic use can have side effects if used incorrectly. Raru wood has pharmacological potential due to its content of secondary metabolites such as flavonoids, tannins, saponins, and triterpenoids. Raru bark extract was developed into a gel dosage form to optimize its treatment effectiveness. The purpose of this study was to determine the gel formulation and antibacterial effectiveness of raru bark extract in the gel preparation. The research method was experimental, involving the formulation and evaluation of the gel, as well as testing its antibacterial activity using the disc method at a concentration of 3%, negative controls, and positive controls.